Molecular effects of the phosphatidylinositol-3-kinase inhibitor NVP-BKM120 on T and B-cell acute lymphoblastic leukaemia. Issue 14 (September 2015) - Pereira, João Kleber Novais; Machado-Neto, João Agostinho; Lopes, Matheus Rodrigues; Morini, Beatriz Corey; Traina, Fabiola; Costa, Fernando Ferreira; Saad, Sara Teresinha Olalla; Favaro, Patricia
Abstract: Background: Constitutive activation of the PI3K pathway in T cell acute lymphoblastic leukaemia (T-ALL) has been reported and in a mouse model, PI3K activation, together with MYC, cooperates in Burkitt lymphoma (BL) pathogenesis. We investigated the effects of NVP-BKM120, a potent pan-class I PI3K inhibitor, in lymphoblastic leukaemia cell lines. Methods: Effects of NVP-BKM120 on cell viability, clonogenicity, apoptosis, cell cycle, cell signalling and autophagy were assessed in vitro on T-ALL (Jurkat and MOLT-4) and BL (Daudi and NAMALWA) cell lines. Results: NVP-BKM120 treatment decreased cell viability and clonogenic growth in all tested cells. Moreover, the drug arrested cell cycling in association with a decrease in Cyclin B1 protein levels, and increased apoptosis. Immunoblotting analysis of cells treated with the drug revealed decreased phosphorylation, in a dose-dependent manner, of AKT, mTOR, P70S6K and 4EBP1, with stable total protein levels. Additionally, we observed a dose-dependent decrease in BAD phosphorylation, in association with augmented BAX:BCL2 ratio. Quantification of autophagy showed a dose-dependent increase in acidic vesicular organelles in all cells tested. Conclusion: In summary, our present study establishes that NVP-BKM120 presents an effective antitumour activity against T-ALL and BL cell lines.